Let x be the number so we write the equation:
\(\displaystyle{x}^{{2}}+{11}={60}\)

Solve for x. Subtract 11 from both sides: \(\displaystyle{x}^{{2}}+{11}-{11}={60}-{11}\)

\(\displaystyle{x}^{{2}}={49}\)

Use the square root property: \(\displaystyle{x}^{{2}}={a}\to{x}=\pm\sqrt{{a}}\)

\(\displaystyle{x}=\pm\sqrt{{49}}\)

x=+-7

-7 and 7

Solve for x. Subtract 11 from both sides: \(\displaystyle{x}^{{2}}+{11}-{11}={60}-{11}\)

\(\displaystyle{x}^{{2}}={49}\)

Use the square root property: \(\displaystyle{x}^{{2}}={a}\to{x}=\pm\sqrt{{a}}\)

\(\displaystyle{x}=\pm\sqrt{{49}}\)

x=+-7

-7 and 7